Designing and implementing a tool to transform source code to UML diagrams (Periodicals of Engineering and Natural Sciences, 2021)
Currently, reverse engineering is considered as a significant process to extract the design information and abstractions of a system from the present software. The extracted source codes have been converted into a certain structure to be easily analyzed in the following procedure. For facilitating the software process development, it might be optimum to have tools beingcertain which generate automatically or help UML generating models from the codes as a source. The current study focuses on the reverse engineering process regarding the python and java source codes to the behavior diagrams: the use case and the activity diagrams which might be of high importance in the process of software maintenance. This approach is carried out in the current study in the application referred to as the RCUML tool with the use of the python language which helped in understanding python and java source codes in the software application, and enabling visualization regarding the software behavior.